NALISIS FRAUD TRIANGLE DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN DENGAN MENGGUNAKAN FRAUD SCORE MODEL - DIRVI SURYA ABBAS; MULYADI; BASUKI; SANI FATIKA (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
Effects of Fraud Triangle Analysis in Detecting Fraud Financial Statements Using the Fraud Score Model on Property and Real Estate Companies Listed on the Indonesia Stock Exchange. The time period of the study is 4 years, namely the 2015-2018 period. This research population includes Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2018 period. The time period of the study is 4 years, namely the 2015-2018 period. Based on the established criteria, 10 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis. The results showed that external pressure and turnover had a significant positive effect on Financial Statement Fraud, and financial stability, ineffe